LEADERSHIP QUALITY DEVELOPMENT FOR STUDENTS IN PROFESSIONAL PREPARATION - Machynska, Nataliya (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the theoretical aspects of leadership as a sociocultural phenomenon, determined features of formation of leadership qualities in students in the conditions of the academic environment of a higher educational institution. The written is based on the patterns and features of management education as a leading concept of educational management in the context of European integration reforms of society, mentioning methodological principles of state and public administration educational institution, offers a meaningful description of the concepts of «leader» and «leadership». The article states that the leader in educational process is a person or institution that carries out activities in the field of education, and leadership is the ability of an individual to act, to «inflate», to inspire others to be active. The author, on the basis of theoretical analysis, determines the peculiarities of teacher-leader and leader in student environment, describes the priorities of the activity of the modern educational leader. The article describes the factors of development of the phenomenon of leadership, in particular: sociological, economic, cultural and personal-oriented. It is shown that one of the effective ways of forming leadership qualities for future specialists in the context of their professional training may be the active introduction of training programs. The author identifies some phenomena of pedagogical interaction, which have a decisive influence on the formation of leadership qualities of students and their clear position of the leader – the phenomenon of trust, reflection of subjectivity, mutual understanding.